A workflow for predicting temperature increase at the electrical contacts of deep brain stimulation electrodes undergoing MRI. Issue 5 (4th July 2022) - Sadeghi‐Tarakameh, Alireza; Zulkarnain, Nur Izzati Huda; He, Xiaoxuan; Atalar, Ergin; Harel, Noam; Eryaman, Yigitcan
Abstract : Purpose: The purpose of this study is to present a workflow for predicting the radiofrequency (RF) heating around the contacts of a deep brain stimulation (DBS) lead during an MRI scan. Methods: The induced RF current on the DBS lead accumulates electric charge on the metallic contacts, which may cause a high local specific absorption rate (SAR), and therefore, heating. The accumulated charge was modeled by imposing a voltage boundary condition on the contacts in a quasi‐static electromagnetic (EM) simulation allowing thermal simulations to be performed with the resulting SAR distributions. Estimating SAR and temperature increases from a lead in vivo through EM simulation is not practical given anatomic differences and variations in lead geometry. To overcome this limitation, a new parameter, transimpedance, was defined to characterize a given lead. By combining the transimpedance, which can be measured in a single calibration scan, along with MR‐based current measurements of the lead in a unique orientation and anatomy, local heating can be estimated. Heating determined with this approach was compared with results from heating studies of a commercial DBS electrode in a gel phantom with different lead configurations to validate the proposed method. Results: Using data from a single calibration experiment, the transimpedance of a commercial DBS electrode (directional lead, Infinity DBS system, Abbott Laboratories, Chicago, IL) was determined to be 88 Ω. Heating predictions using the DBS transimpedance and rapidly acquired MR‐based current measurements in 26 different lead configurations resulted in a <23% (on average 11.3%) normalized root‐mean‐square error compared to experimental heating measurements during RF scans. Conclusion: In this study, a workflow consisting of an MR‐based current measurement on the DBS lead and simple quasi‐static EM/thermal simulations to predict the temperature increase around a DBS electrode undergoing an MRI scan is proposed and validated using a commercial DBS electrode.